Skin self-examination behaviors among individuals diagnosed with melanoma. Issue 1 (February 2016) - Coups, Elliot J.; Manne, Sharon L.; Stapleton, Jerod L.; Tatum, Kristina L.; Goydos, James S.
Abstract : Many melanoma patients do not regularly perform thorough skin self-examinations. We examined the extent to which melanoma patients conduct thorough skin self-examination, how they perform skin self-examination, and their related knowledge and self-efficacy. A sample of 176 individuals (61.5% response rate) diagnosed with primary pathologic stage 0–III cutaneous malignant melanoma at a single cancer center completed a written or telephone survey regarding their skin self-examination behaviors and associated factors. Almost all participants (98.9%) reported their race as white. Almost three-quarters (71.6%) of participants reported doing an examination in the past 2 months. However, only 14.2% had examined all areas of the body in the past 2 months. Few participants reported always using a full-length mirror (13.4%), hand-held mirror (11.3%), or having someone help (9.2%) when doing an examination. Having a higher level of education, greater knowledge of the ABCDE rule for detecting potential melanoma, higher skin self-examination self-efficacy, being shown how to do skin self-examination, and being shown what a suspicious mole would look like were all significantly associated with conducting more thorough skin self-examination. Most melanoma patients do not engage in regular, thorough skin self-examination, and when they do examine their skin they typically do not sufficiently utilize tools and techniques to facilitate a thorough examination and tracking of potentially suspicious moles. Efforts to promote skin self-examination among melanoma patients should focus on increasing knowledge and self-efficacy and providing education about the why, when, and how of conducting self-examination and mole tracking.